Frequency of Electrolytes Abnormalities in Cirrhotic Patients Presenting with Hepatic Encepahlopathy - Khattak, Shahnawaz Yousaf; Ahmad, Nafees; Khattak, Mehmood; Mahmood, Bakhti; Abdul Quddos,; Khan, Mobeen Ali (Indus Journal of Bioscience Research, 2025)
Background: Hepatic encephalopathy (HE) is a serious complication of liver cirrhosis, characterized by neuropsychiatric impairments that significantly impact patient morbidity and mortality. Electrolyte abnormalities, particularly hyponatremia and hypokalemia, are common in cirrhotic patients and are known to exacerbate HE. This study aims to determine the frequency of electrolyte abnormalities in cirrhotic patients presenting with HE and their association with clinical variables. Methods: A descriptive cross-sectional study was conducted over six months at the Department of Medicine, Khyber Teaching Hospital, Peshawar. A total of 60 cirrhotic patients with HE, aged 20–70 years, were included using non-probability sampling. Serum sodium and potassium levels were measured to identify hyponatremia (<125 mmol/L) and hypokalemia (<3.5 mmol/L). Data were analyzed using SPSS version 20, with mean and standard deviation calculated for numerical variables and frequencies and percentages for categorical variables. Stratification was performed based on age, gender, and grades of hepatic encephalopathy, with statistical significance assessed using the chi-square test (p < 0.05). Results: The study found a high prevalence of electrolyte abnormalities, with hyponatremia observed in 75% of patients and hypokalemia in 50%. Both abnormalities were present in 33.3% of cases. Patients aged 41–50 showed the highest abnormalities prevalence (86.7%), followed by the 51–60 age group (76.9%). Stratification by hepatic encephalopathy grade revealed that Grades III and IV were associated with significantly higher rates of electrolyte disturbances (86.7% and 80%, respectively; p < 0.01). Gender was not significantly associated with electrolyte abnormalities (p > 0.05). Conclusion: Electrolyte abnormalities, particularly hyponatremia and hypokalemia, are highly prevalent in cirrhotic patients with hepatic encephalopathy, especially in middle-aged individuals and those with advanced disease grades. Early identification and correction of these disturbances are critical to improving clinical outcomes and reducing morbidity in this vulnerable population.